Prevalence and pain distribution of anterior knee pain in collegiate basketball players - Hannington, M.; Tait, T.; Docking, S.; Cook, J.; Owoeye, O.; Bonello, C.; Emery, C.; Pasanen, K.; Edwards, S.; Rio, E. (Journal of Athletic Training, 2022)
Context: Causes of anterior knee pain (AKP) in jumping athletes include patellofemoral pain and patellar tendinopathy. The differential diagnosis of AKP is challenging, with variations in clinical presentations. No previous research has used pain location to describe AKP in basketball players.